Pathological and biochemical descriptors of Ralstonia solanacearum of tomato (Solanum lycopersicum) in Tanzania - Aloyce, A; Ndakidemi, P A; Mbega, E R (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted to identify bacterial wilt disease-causing isolates of Ralstonia solanacearum (Smith) in Tanzania. The pathological and biochemical descriptors were used to determine the virulence and biovars of 40 bacterial isolates originating from 200 wilted tomato (Solanum lycopersicum L.) stems collected from the main agro ecological zones of Tanzania. Results revealed that 53% of the investigated isolates were pathogenic, whereas 90% of isolates belonged to biovar 3 and the rest (10%) were biovar 2. Biovar 3 was present in all of the surveyed agroecological zones, whereas biovar2 prevailed in Southern zone only and is reported for the first time in Tanzania. This is an alert for plant health officers to implement standard phytosanitary measures in preventing new introduction and spread of Ralstonia to uninfected locations. Descriptors adopted successfully identified biovars of Ralstonia, thus can be integrated with other diagnosis tools to manage bacterial wilt disease.